Theoretical study on influence of steel composition on solidification behaviour in ingot casting of low alloy steels at similar casting conditions. (April 2015) - Patil, P.; Marje, V.; Balachandran, G.; Balasubramanian, V.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of chemical composition of four different steel grades on solidification of 4 MT ingot at similar casting conditions has been examined using finite element model. As a consequence of change in grade dependent thermophysical properties, variations were obtained in velocity of the solidifying metal, which varied with carbon content, temperature distribution, mushy zone formation, porosity and piping. Microsegregation, which is measured by local solidification time, increased with increasing carbon content due to variation in solidus and liquidus. Alloy steels were found more prone to formation of shrinkage and central porosity compared to carbon steels. It is observed that solidification behaviour could not be related to specific thermophysical property, and combination of thermophysical properties and the alloy solidification characteristics affect the same. Improvement in alloy steel ingot quality was achieved through variation in hot top design. This study shows that steel ingot quality and yield is affected by subtle changes in composition.